Disseminated BCG Infection (BCGosis) After BCG Vaccination - Poudel, P; Chitlangia, M (Journal of Nepal Paediatric Society, 2014)
BCG vaccine has excellent safety profile. Disseminated BCG infection, so called BCGosis and death have occurred in few cases, mainly in those with impaired immunity. We are reporting a seven month old infant who developed BCGosis after BCG vaccination. She presented with weight loss, fever, axillary lymphadenopathy and hepato-splenomegaly. She did not respond to standard antitubercular treatment. In the context of increasing number of reported cases of BCGois in HIV era, inoculation of BCG might be postponed in a suspected case of immune-deficiency disease, until it is ruled out. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9679 J Nepal Paediatr Soc 2014;34(1):62-64